Mobile Game Effectiveness for Game Enthusiasts Who Have Little Spare Time to Play Games - Nuryanti, Nuryanti; Prasetya, FX Hendra (Soegijapranata Catholic University, 2015)
The development of technology continues to increase. As well as the development of game that pamper the player. But on the other hand,with the increasing development of technology, gamerâs demand will also be higher as well. As example, technological devices to play games should be more practical, light, and easy to carry anywhere. This paper will discuss about the effectiveness of mobile game for game enthusiasts